Rogue Christmas operation - Rushdan, Juno (Rushdan, Juno. Fugitive heroes: Topaz unit, 2021)
"After Gage Graham saves her from drowning, Hope Fischer revives, determined to learn the truth about her sister's death. All she has to do is infiltrate a mysterious closed Virginia town and discover why the attractive--but secretive--Gage feels compelled to help her. Can she trust him? Will he risk being discovered by his former employer, the CIA, for a woman he just met? Neither will matter if a killer succeeds" --